Conservation Agriculture for Enhancing resource-use efficiency in maize systems - Parihar, C. M.; Singh, A. K.; Jat, S. L. (Indian Farming, 2015)
Conservation agriculture based management practices in maize systems are helpful in achieving the higher profitability with lesser environmental as well as natural resources degradation, improved/ sustained soil health and quality and addition of more organic matter. These crop management practices also provide opportunities for crop intensification and diversification in the shrinking arable land and increasing population scenarios. Moreover, these management practices are helpful in reducing major input cost of farming incurred towards tillage operations. Thus, CA is a way forward towards enhancing food production and farm profitability with environmental benefits from agriculture.